Morbidity and Mortality of Very Low Birth Weight Infants with Congenital Heart Disease - Song, Woo Sun (Korean Circ J, 2020)
BACKGROUND AND OBJECTIVES: This study aimed to provide morbidity and mortality information on very low birth weight (VLBW) infants with congenital heart disease (CHD-VLBWs). METHODS: The study used a 10-year cohort of VLBW infants from a single institution. CHD was classified according to International Classification of Diseases, Version 9, Clinical Modification. Mortality and neonatal outcomes were assessed by comparing the CHD-VLBWs with gestational age- and birth weight-matched controls. RESULTS: The prevalence of CHD-VLBWs was 7.5% (79/1,050), mean gestational age was 31.1±3.2 weeks, and mean birth weight was 1,126.2±268.3 g; 50.6% of the infants were small for the gestational age. The CHD-VLBWs more commonly had bronchopulmonary dysplasia (BPD), and the longer they were exposed to oxygen, the more frequently they developed BPD. Those with cyanotic heart disease developed severe BPD more frequently. Necrotizing enterocolitis (NEC) occurred frequently in the CHD-VLBWs and was not associated with their feeding patterns. CHD-VLBWs had a higher mortality rate; prematurity-related diseases were the leading cause of death before surgery, while heart-related problems were the leading cause of death after surgery. We found no significant difference in mortality from prematurity-related disease between the CHD-VLBWs and controls. In the subgroup analysis of CHD, the cyanotic CHD group had a higher incidence of BPD and higher mortality rate than the acyanotic CHD group. CONCLUSIONS: CHD-VLBWs showed higher BPD, NEC, and mortality rates than those without CHD. There was also a higher incidence of BPD and mortality in VLBW infants with cyanotic CHD than in those with acyanotic CHD.